2013
DOI: 10.4137/ccrpm.s12525
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Resting pulmonary Function in Heart Failure

Abstract: BackgroundThe heart and lungs are intimately linked anatomically and physiologically, and, as a result, heart failure (HF) patients often develop changes in pulmonary function. This study examined the prognostic value of resting pulmonary function (PF) in HF.Methods and resultsIn all, 134 HF patients (enrolled from January 1, 1999 Through December 31, 2005; ejection fraction (EF) = 29% ± 11%; mean age = 55 ± 12 years; 65% male) were followed for 67 ± 34 months with death/transplant confirmed via the Social Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 48 publications
1
28
0
2
Order By: Relevance
“…5 Structural and functional alterations of the lungs in HF are well described 5,6 and correlate to HF severity and patient survival. 7 Therefore, it is hypothesized that the alteration in CF LVAD influences pulmonary function (PF) and is related to survival rate. However, knowledge is still lacking about the long-term effect of CF pumps on the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Structural and functional alterations of the lungs in HF are well described 5,6 and correlate to HF severity and patient survival. 7 Therefore, it is hypothesized that the alteration in CF LVAD influences pulmonary function (PF) and is related to survival rate. However, knowledge is still lacking about the long-term effect of CF pumps on the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study reporting the association between spirometric parameters and outcomes in this population. Studies investigating the prognostic value of spirometry in subjects with acute 25 or stable 24,26 heart failure showed that spirometric variables predict outcomes in these stage C heart failure populations. However, we did not observe a similar association in our study, in which we included subjects with stage D heart failure exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Specifically to heart failure, spirometric parameters have been demonstrated to predict incident heart failure [21][22][23] and outcomes of patients with stage C heart failure. 17,[24][25][26] However, the association of spirometric parameters with outcomes in patients with advanced (stage D) heart failure listed for heart transplantation is less clear. Patients referred for heart transplantation represent a more homogeneous population in which left ventricular function is severely impaired and congestive symptoms are common.…”
Section: Introductionmentioning
confidence: 99%
“…3 The co-existence of COPD and HF is often a therapeutic and diagnostic challenge in HF management, 4 and COPD in patients with HF is associated with a worse clinical status and an increased risk of cardiovascular death and hospitalizations. 12 The mechanism behind these findings, however, is unresolved. [6][7][8][9] It is well known that patients with congestive HF (CHF) have a reduction in pulmonary diffusion capacity for carbon monoxide (D LCO ), 1 and CHF is known to increase the resistance to gas transfer across the alveolarcapillary membrane.…”
Section: Introductionmentioning
confidence: 99%
“…10 Some studies have shown that a reduced diffusion capacity contributes to exercise intolerance 11 and is a predictor of mortality in HF patients. 12 The mechanism behind these findings, however, is unresolved. It is clear that cardiopulmonary interaction is an important element in HF pathophysiology.…”
Section: Introductionmentioning
confidence: 99%